PENGARUH PENERAPAN SUNSET POLICY PBB PERKOTAAN TERHADAP KEMAUAN MEMBAYAR PAJAK DAN KEPATUHAN WAJIB PAJAK (STUDI PADA WAJIB PAJAK ORANG PRIBADI YANG BEKERJA DI KANTOR AKUNTAN PUBLIK, KANTOR KONSULTAN PAJAK, DAN KANTOR JASA PENILAI PUBLIK DI KOTA MALANG) - Amelia Renata Usman (Jurnal Ilmiah Mahasiswa FEB, 2016)
The Impact Of Sunset Policy Of Urban Land And Building Tax On The Willingness Of Taxpayers To Pay Tax And Their Compliance To Tax (A Study On Individual Tax Payers Working In Public Accountant Firm, Tax Consultant Firm, And Public Appraisal Firm In Malang). This research aims at analyzing the impact of the application of sunset policy of urban land and building tax on the willingness of taxpayers to pay tax  and their compliance to fulfill their taxation obligation. Sunset policy is an abolishment of tax administrative sanction charged to tax tardiness or tax in arrears in a particular period. This policy is expected to increase social willingness to pay tax and to improve tax payer’s compliance. This research uses primary data obtained from questionnaires distributed to 75 individual tax payers whose profession are accountants, auditors, tax consultants, and appraisers working in Public Accountant Firms, Tax Consultant Firms, and Public Appraisal Firms in Malang. The sampling method used in this research is judgement-type purposive sampling. The hypothesis is analyzed using Partial Least Square (PLS) with SmartPLS. The result of this research shows that sunset policy positively influences the willingness to pay tax and improves tax payer’s compliance. This means that the application of sunset policy of urban land and building tax can increase willingness to pay tax and tax payer’s compliance.Key words: sunset policy, willingness to pay tax, tax payer’s compliance